Shading in the late stem elongation period generate the greatest grain yield reduction in oat (Avena sativa L.). Issue 10 (24th August 2023) - Dietz, Juan Ignacio; Da Silva, Laura; Schierenbeck, Matías; Simón, María Rosa
ABSTRACT: This study was carried out to determine the critical period in oats, which is relevant for locating that period under the best climatic conditions. Trials were conducted in the Argentinian Pampas during 2015–2016, using four oat genotypes with different growing cycle. The experimental design was a split-split-plot, with three replications; being genotypes the main plot and the subplots six shading treatments [unshaded control and five shaded treatments during 25 days, from different growth stages [GS31 (first-visible-node), GS32, GS33, GS40 (boot), and GS60 (flowering)]. GY and its components [(number of panicles (NP), grains number per panicles (GNP), grains number per square meter (GN), and thousand kernel weight (TKW)] were determined at harvest. GY was sensitive to radiation limitations, showing falls of 20 to 70%, varying according to shading and genotypes. The shading mainly affected GY between GS32 and a few days after flowering in the short-intermediate cycle genotypes, and from GS33 in those with the longest cycles. Regression analysis showed that GN was the most affected yield component, being GNP more sensitive to stress and closely related to GN than NP. TKW showed less magnitude reductions (4.6 to 17.4%), being the shading at GS40, the one that caused the greatest decreases.